Aligning Sabah foundation education scholarship with employability: Strategies for bridging the gap - Nesin Elizabeth Kinat; Nelson Lajuni,; Dinisiah Liasan; Zulaikha Hj. Abdul Kassim (International Research Journal of Education and Sciences (IRJES), 2024)
This paper explores the intersection of education scholarship and employability, aiming to elucidate the role of Sabah Foundation education scholarship in narrowing the gap between educational outcomes and workforce readiness. It examines the challenges and opportunities in fostering alignment between education and employability, emphasising the importance of equipping learners with the knowledge, skills, and competencies demanded by the evolving labour market. This paper elucidates effective strategies for integrating employability-focused initiatives into educational systems by synthesising research, case studies, and best practices. By promoting collaboration among educators, employers, policymakers, and other stakeholders, education scholarship can catalyse enhancing employability outcomes and facilitate successful transitions from education to the workforce.